Determination of the Shortest Route with the Djikstra Algortima in the Operation of Aplousing and Maintenance of Shipping Navigation Aids (SBNP) - Efendi, Ade Irfan; Kusuma, Wisnu Wardana; Wanadi, M Adil Wanadi; Rizal, Yus; Prakosa, Dandun (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to implement the djikstra algorithm to overcome the problem of optimizing the shortest route determination in aplousing and maintenance activities of Shipping Navigation Assistance Facilities (SBNP) in the working area of the Tanjung Perak Type A Navigation District Office. The Navigation Pier has historically been a strategic facility to face the challenges of maintaining fuel efficiency, sailing times and reducing emissions in environmental pollution due to suboptimal routes. The djikstra algorithm is known to be effective in finding the shortest route on a weighted graph by representing strategic location points such as ports and marine navigation areas as nodes and the distance between nodes is calculated using the haversine formula based on geographic coordinates as weights. Before the implementation of travel route optimization, a total mileage of 1,210.30 km was obtained and after the optimization was applied using the djikstra algorithm, a total mileage of 1,110.44 km was obtained. This comparison shows a significant distance savings of 99.86 km or 8.25% travel efficiency. This optimization is able to contribute to time reduction, fuel savings and reduction of environmental pollution exhaust gas emissions so that it is able to optimize the operational effectiveness of ships as a whole. This study confirms the positive and relevant capabilities to be applied in shipping navigation route planning and support decision-making in the management of sea routes or logistics transportation in areas with a varied distribution of mileage points that require high efficiency and mobility. In the next research, it is hoped that it will be able to add external factors such as sea currents, waves, and wind according to the geographical characteristics of the territorial waters so that the results of route planning can be more accurate in the real operational area in the shipping work area.